Development of microemulsion of a potent antityrosinase essential oil of an edible plant - Kiattisak Saeio (2018)
The aim of this study is to develop a microemulsion product from a plant essential oil having the highest antityrosinase activity. The in vitro antityrosinase activity of six essential oils extracted from six edible plants was compared. The oil of Cymbopogon citratus demonstrated the highest activity which was significantly nontoxic to normal human cells. The GC-MS data indicated that geranial and neral are the major compounds in the oil. The phase diagram composed of C. citratus oil, water, and surfactant mixture was conducted by a titration method. Ethyl alcohol was found to be the most suitable cosurfactant for the C. citratus oil microemulsion. The results revealed that the amount of oil and water played an important role in microemulsion conductivity and type. The most desirable o/w type of C. citratus oil microemulsion was found to be composed of 20% oil, 30% water, and 50% surfactant mixture of a 2:1 weight ratio of Tween 20 and ethyl alcohol. © 2011, International Research and Cooperation Association for Bio & Socio-Sciences Advancement. All rights reserved.